2024
DOI: 10.1029/2023je007919
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a Lake Margin Recorded in the Sutton Island Member of the Murray Formation, Gale Crater, Mars

S. Gwizd,
C. Fedo,
J. Grotzinger
et al.

Abstract: This study uses data from the Mars Science Laboratory Curiosity rover to document the facies of the Sutton Island member of the Murray formation, interpret paleoenvironments, and establish key stratigraphic transitions at Gale crater. Two facies associations were identified: Facies Association 1 (FA1) and Facies Association 2 (FA2). Individual facies in FA1 include planar‐laminated mudstone with minor intervals of planar sandstone, ripple cross‐laminated sandstone, cross‐stratified sandstone, and alternating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 97 publications
(192 reference statements)
1
9
0
Order By: Relevance
“…However, this interpretation was based on the larger scale of the outcrops and the intervals of cross stratified sandstones in those outcrops that likely indicate a dune setting (Gwizd et al, 2022). Blocks in Sutton Island are more broken up than in continuous outcrops, making this interpretation more difficult; Gwizd et al (2023) showed that the changes in Sutton Island bedrock likely represent a change in lake water level. The higher portion of Sutton Island likely represents the channel outlet near the shore of the lake (Gwizd et al, 2023).…”
Section: Deposition Of Sandstone At Newport Ledge In a Subaqueous Plu...mentioning
confidence: 99%
See 4 more Smart Citations
“…However, this interpretation was based on the larger scale of the outcrops and the intervals of cross stratified sandstones in those outcrops that likely indicate a dune setting (Gwizd et al, 2022). Blocks in Sutton Island are more broken up than in continuous outcrops, making this interpretation more difficult; Gwizd et al (2023) showed that the changes in Sutton Island bedrock likely represent a change in lake water level. The higher portion of Sutton Island likely represents the channel outlet near the shore of the lake (Gwizd et al, 2023).…”
Section: Deposition Of Sandstone At Newport Ledge In a Subaqueous Plu...mentioning
confidence: 99%
“…Gale's central mound, Aeolis Mons (informally "Mount Sharp"), rises 5 km above the crater floor, Aeolis Palus, and is largely comprised of sedimentary rocks (Fraeman et al, 2016;Malin & Edgett, 2000;Milliken et al, 2010). Gale is interpreted as having hosted a habitable redox-stratified lake or series of lakes in its past based on chemical, mineral, and stratigraphic evidence of hematite and phyllosilicate-bearing fluvial-deltaic deposits and lacustrine mudstones (Edgar et al, 2020;Grotzinger et al, 2014Grotzinger et al, , 2015Gwizd et al, 2022Gwizd et al, , 2023Hurowitz et al, 2017;Vaniman et al, 2014). The Gale lake produced 100s of meters of typically fine-grained thinly laminated lake sediment deposits, collectively named the Murray formation (Edgar et al, 2020;Rivera-Hernández et al, 2020).…”
Section: Geologic Contextmentioning
confidence: 99%
See 3 more Smart Citations